ECO GREEN HOUSING TECHNOLOGIES TALK – STRENGTHENS THE KNOWLEDGE AND SKILLS OF STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PULAU PINANG, November 2015 – PU Profile Sdn. Bhd., a joint venture Multinational company between Malaysia, Brunei, Canada and Belgium, based in Perak Darul Ridzwan, conducted a talk on Eco Green Housing Technologies to the students and lecturers of the School of Housing, Building and Planning (HBP) Universiti Sains Malaysia (USM) recently.